Food for Tomorrow - Shevchenko, Vasily; Pylypiva, Catherine (My University, 2014)
Molecular Gastronomy blends physics and chemistry to transform the tastes and textures of food. The result? New and innovative dining experiences.
Keywords: molecular gastronomy; gastronomic phenomena; молекулярна гастрономія; гастрономічний феномен; кафедра іноземних мов професійного спрямування